(untitled) (Journal of Global Humanities and Social Sciences, 2023)
In the healthcare field, the doctor-patient relationship is an important factor in ensuring the quality of care and patient satisfaction. However, in the past, there have been problems of detachment and miscommunication between doctors and patients, which have negatively impacted medical outcomes and patient experience. Therefore, it has become particularly important to focus on building and improving the culture of healthcare organizations. The culture of a healthcare organization has a profound impact on the doctor-patient relationship, which includes aspects of trust and communication, doctor-patient collaboration and shared decision-making, respect, and empathy. By building a culture that promotes trust and communication, medical staff can build strong ties with patients and facilitate information exchange and shared decision-making. At the same time, healthcare organizations should develop cultural sensitivity and cross-cultural competence among medical staff to better understand and respect patients from different cultural backgrounds. Through these efforts, healthcare organizations can improve the doctor-patient relationship, enhance the quality of care, and achieve more satisfying medical outcomes.